The WTO Impact on International Trade Disputes: An Event History Analysis - Grinols, Earl L; Perrelli, Roberto (The Review of Economics and Statistics, 2006)
Many consider improved dispute settlement one of the leading achievements of the WTO. This paper tests the implication of a game-theoretic approach that predicts that more efficient litigation devices increase the frequency and number of trade disputes. We propose an empirical event history analysis of GATT, WTO, and USTR Section 301 cases, identify the demographic patterns for births and lifespans of U.S. disputes, and test the hypothesis of a WTO structural break. The evidence supports the view that the WTO increased the incidence of U.S. trade disputes, while shortening their lifespan.